Co-opetition and urban worlds, c. AD 1050-1150: archaeological and textual case studies from northwestern Europe - Loveluck, Chistopher (Brepols, 2018)
This article explores the complex combinations of collaborative and competitive social relations that catalyzed the development of towns and urban societies in northwestern Europe, during the century between c. AD 1050 and 1150. It aims to evaluate the initiative or agency of different social groups in the formation of different urban social fabrics. Case studies are considered from major port cities and centres of regional (and sometimes state) government, to small ports and even rural villages that carried the judicial status of towns. Both archaeological and textual evidence is utilized to try to shed light on the nature of different urban societies and how they developed. The regional scope of the case studies encompasses examples principally from England, France and Flanders, with some additional comparative material from Wales and northern Iberia.